(untitled) (Modern education and development, 2024)
Although the topic of Ottoman tourists with its rich history, especially the small Asian tourists who traveled to different parts of the world such as Africa and Europe, has been studied in some depth, it is in the Asian continent, especially in Central Asia, that the history, socio-political, economic and ethno-cultural aspects of these regions The topic of tourists who witnessed the processes with their own eyes is not covered enough